PENGARUH PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN DENGAN TRANSPARANSI PERUSAHAAN SEBAGAI VARIABEL MODERASI - Pradnyana, Ida Bagus Gede Putra; Noviari, Naniek (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
Another way to preserve firm value is tax planning. This done, so tax payer can pay their taxes effectively and efficiently and maintain company's image. Corporate transparency shown by how much information is disclosed by management to company owners and this expect to reduce odds of opportunistic management when doing tax planning. This can reduce asymmetry information which also reduces conflicts of interest and support of enhancement the firm value. This study was to obtain empirical evidence on firm value of the effect of tax planning with corporate transparency as moderating variable. This research conducted at consumer goods company listed on Indonesia Stock Exchange in year 2013-2015. Number of samples is 72, with purposive sampling techniques. The analysis technique used is moderated regression analysis (MRA). Results of study are variable tax planning affect the firm value. Corporate transparency as a moderating variable amplified effect of tax planning on firm value.
Keywords: Tax planning, Corporate transparency, Firm value